Liver steatosis is positively associated with plasminogen activator inhibitor-1 in apparently healthy individuals with overweight and obesity: A FibroScan-Based Cross-Sectional study - Giuseppe Lisco; Davide Guido; Nicole Cerabino; Martina Di Chito; Rosanna Donvito; Caterina Bonfiglio; Endrit Shahini; Marianna Zappimbulso; Cristiana Randazzo; Domenico Barletta; Dolores Stabile; Anna Ancona; et al. (Journal of Translational Medicine)
Abstract Background Metabolic dysfunction-associated steatotic liver disease (MASLD) is the most common cause of steatotic liver disease and has major implications on cardiovascular safety. Study aims As the precise role linking MASLD to cardiovascular diseases is still unclear, the present study aims to investigate the association between liver steatosis and fibrosis and circulating plasminogen activator inhibitor-1 (PAI-1) levels. Methods Eighty-two patients (41.6 ± 12.4 yrs, 34 men, 41%), naïve to medications, who attended the Nutrition Center for the Research and Care of Obesity and Metabolic Diseases at the National Institute of Gastroenterology “Saverio de Bellis” for weight management, were cross-sectionally evaluated. Demographic, anthropometric, clinic, and laboratory data were collected and analyzed. All patients underwent liver ultrasonographic assessment by FibroScan to diagnose liver steatosis (controlled attenuation parameter or CAP > 275 dBm) and fibrosis (liver stiffness > 8.2 kPa). Results Sixty-one individuals (74.4%) had liver steatosis, and 17 (20.7%) had liver fibrosis. PAI-1 mean levels were 3,261 ± 1,270 pg/mL, mean body mass index (BMI) and waist circumference (WC) values were 36.6 ± 7.1 kg/m2 and 114.1 ± 16.5 cm, respectively. Mild systolic and diastolic arterial pressure elevation and significantly high values of fasting plasma insulin (19.6 ± 12.6 IU/mL) and homeostatic model assessment of insulin resistance or HOMA-IR (4.8 ± 3.5) were also found. CAP values were correlated with several anthropometric, clinical, and laboratory parameters of insulin resistance. We found a significant association between PAI-1 and CAP (β = 1.605; p = 0.004), and noteworthily, when PAI-1 increased by 100 units, the expected variation of CAP values was by + 1.6 units (p = 0.004). Notably, the association was independent of gender, age, and insulin resistance. Discussion Circulating PAI-1 levels are correlated with liver steatosis and, to a lesser extent, fibrosis in apparently healthy patients with a BMI ≥ 25 kg/m2. This is the first study to show these results in patients naïve to medications, using FibroScan assessment. The bidirectional relationship between circulating PAI-1 levels and CAP measurement highlights the relevance of our research from a diagnostic and pathophysiological-prognostic viewpoint. Longitudinal trials are needed to clarify the cause-effect association between MASLD and PAI-1 levels.